Adenoma Recurrence after Endoscopic Piecemeal Mucosal Resection of Colorectal Flat Lesions: Applicability of the Sydney EMR Recurrence Tool in a Non-Tertiary Centre - Silva,Maria Azevedo (2022)
Abstract Introduction: Endoscopic mucosal resection (EMR) is the treatment of choice for non-invasive colorectal flat lesions. When endoscopic piecemeal mucosal resection (EPMR) is performed, endoscopic surveillance is necessary due to the risk of recurrence. The Sydney EMR Recurrence Tool (SERT) is a 0-4 scale that classifies lesions according to size, occurrence of intraprocedural bleeding (IPB) and presence of high-grade dysplasia (HGD). Our goal is to evaluate the applicability of SERT in predicting adenoma recurrence (AR) after EPMR. Methods: This is a retrospective single-centre study with inclusion of lateral spreading lesions ≥20 mm, consecutively resected by EPMR from March 2010 to February 2018, with at least 1 endoscopic re-evaluation. Results: A total of 181 lesions were included, corresponding to 174 patients with a mean age of 68 years and male gender predominance (61%; n = 106). The most frequent location was the ascending colon (34%; n = 62). Lesions were assessed according to Paris Classification (PC): 0-IIa: 39% (n = 71); 0-IIb: 24% (n = 43); 0-IIa + Is: 23% (n = 42); 0-IIa + IIb: 6% (n = 11); 0-IIa + IIc: 2% (n = 3). The mean size of the lesions was 33 ± 11 mm, with 25 (14%) being ≥40 mm. IPB occurred in 9 cases (5%), and 44 lesions (24%) displayed HGD. Sixty-six lesions (36.5%) were classified as SMSA (size, morphology, site, and access score) level 4. Adjunctive therapy with argon plasma coagulation (APC) was used in 37% (n = 67) of cases. The 6-month AR rate was 16% (n = 29). According to SERT groups, the AR rate was: SERT 0: 12% (14/120); SERT 1: 17% (6/35); SERT 2: 25% (3/12); SERT 3: 30% (3/10); SERT 4: 75% (3/4). Two of the three SERT variables (size ≥40 mm and IPB) were associated with recurrence at 6 months (p < 0.05). HGD and the remaining tested variables (age, gender, localization, accessibility, PC, use of APC/biopsy forceps and occurrence of delayed bleeding) were not associated with AR. SERT 0 lesions showed an inferior risk of 6-month AR (adjusted OR = 2.62; p = 0.035), with a negative predictive value of 88%. SMSA correlated with SERT (p < 0.001) and SMSA level 4 was associated with 6-month AR (p = 0.007). Lesions classified both as SERT 0 and SMSA level <4 had the lowest 6-month recurrence rate (9.2%). The 24-month recurrence rate was 23% (n = 41). When applying the Kaplan-Meier method, cumulative recurrence was significantly lower in SERT 0 lesions (p = 0.006, log-rank test). Discussion/Conclusion: Resection of flat colorectal lesions by EPMR has a considerable risk of recurrence, mostly in SERT 1-4 lesions. SERT 0 lesions, especially with SMSA level <4, show a lower risk of recurrent adenoma, which might allow longer intervals to first endoscopic surveillance in the future.